2015
DOI: 10.1007/s10461-015-1159-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Peer Support on Care Engagement and Preventive Care Intervention Utilization Among Pre-antiretroviral Therapy, HIV-Infected Adults in Rakai, Uganda: A Randomized Trial

Abstract: 442 pre-ART, HIV-infected adults were randomized to peer support consisting of structured home visits to promote clinic attendance and preventive care intervention use or standard of care. At baseline, 62% reported previously visiting an HIV clinic, 45% reported taking cotrimoxazole prophylaxis, and 31% were “care-naïve” (no previous clinic visit and not on cotrimoxazole). After one year, intervention participants were more likely to report being in care (92% vs 84%; PRR 1.09, p=0.039), on cotrimoxazole (89% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…A reduction in stigma may help explain results that showed that participants visited by a peer supporter were more likely to use the clean water vessel [24]. The qualitative evaluation revealed that the water vessels were viewed as stigmatizing by a number of people living with HIV because they were different from other water vessels in the area and were specifically associated with HIV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in stigma may help explain results that showed that participants visited by a peer supporter were more likely to use the clean water vessel [24]. The qualitative evaluation revealed that the water vessels were viewed as stigmatizing by a number of people living with HIV because they were different from other water vessels in the area and were specifically associated with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…However, some participants insisted the opposite, that clients in the intervention arm were influenced by peer supporter counseling to reduce their number of sexual partners or increase condom use. These potentially contrasting effects may have contributed to the lack of a difference in sexual behaviors [24]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were individually randomized trials. The interventions were lay counsellor home visits after a home-based CD4 count [8]; lay counsellor clinic visit facilitation [8]; home visits, calls and text messages by patient navigators [9]; home visits by peer supporters [10]; and provision of an informational brochure to patients explaining how to obtain further care [11]. Rates of ART initiation among control-arm patients eligible for treatment were low, at only 32% when pooled across the four studies.…”
Section: Counselling and Support Interventionsmentioning
confidence: 99%
“…The goal-setting and peer meeting intervention components need to be tested in a larger trial with greater rigour and a sufficient sample, using standardised measures, to properly ascertain their effectiveness. A larger study should consider results from other peer support trials, such as a null effect on antiretroviral adherence due to low-intensity (ie, phone support) interventions39 and significant results in adherence and care retention through home visits 40. Future research on postdischarge peer support with a complex population group should therefore explore more intensive supports than weekly phone contact; in-person follow-up, whether meeting in social spaces (such as coffee shops), home visits or outpatients returning to hospital for postdischarge peer groups could be combined with phone calls as more supportive methods of retaining people in care.…”
Section: Discussionmentioning
confidence: 99%